PENGARUH DEBT TO EQUITY RATIO (DER), DEBT TO ASSET RATIO (DAR), DAN INVENTORY TURNOVER TERHADAP PROFITABILITAS PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Komang Putri Aristiani; I Wayan Sukadana; I Wayan Widnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Profitability refers to a comparison to find out the company's ability to get profit from earnings (earnings) related to sales, assets, and equity based on certain measurement basis. This study aims to examine and obtain empirical evidence of the effect of debt to equity ratio (DER), debt to asset ratio (DAR), and inventory turnover on profitability in automotive companies listed on the Indonesia Stock Exchange. The population of this research is automotive companies listed on the Indonesia Stock Exchange in the period 2015-2017. The samples in this study were 13 automotive companies determined based on the purposive sampling method. The tool used to wash away hypotension is SPSS version 23.0 for Windows. The results of this study indicate that the debt to equity ratio (DER), inventory turnover has no effect on profitability. While the debt to asset ratio (DAR) has a negative and significant effect on profitability. Future studies can develop this research by using other variables that theoristically have an influence on profitability.